The Role of Principal Leadership in the Development of Islamic Education Management - Lexy Sutansyah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The development of Islamic education management in madrasahs continues to face various challenges, particularly regarding the optimization of principals' leadership in managing institutional resources, improving teacher quality, and integrating Islamic values into educational practices. These challenges highlight the strategic role of school principals in ensuring the effectiveness of Islamic education management. This study aims to describe and analyze the principal's leadership role in developing Islamic education management at MTs SA Al-Mukarrim Kiarakoneng, Neglasari, Tasikmalaya. The study employed a qualitative method with a case study approach. Data were collected through in-depth interviews, direct observations, and documentation and analyzed using descriptive qualitative techniques. The findings indicate that the principal effectively performs multiple leadership roles as a manager, supervisor, motivator, and innovator in developing Islamic education management. These roles are reflected in strategic school management, teacher professional development, the strengthening of organizational culture, and the integration of Islamic values into all aspects of educational administration. The study concludes that visionary, collaborative, and values-based leadership is a key determinant in establishing effective Islamic education management and achieving the vision and mission of the madrasah. This study contributes to the growing body of knowledge on educational leadership by providing empirical evidence on the critical role of principals in strengthening Islamic education management within the context of Indonesian madrasahs.